PENERAPAN METODE RAPID APPLICATION DEVELOPMENT (RAD) DALAM PENGEMBANGAN APLIKASI SIMPAN PINJAM KOPERASI SYARIAH - Kosidin; Edi; Ana (POLITEKNIK PIKSI GANESHA, 2020)
There are many methods that can be used in the manufacture and development of an information system application but in the implementation of this research using the Rapid Application Development (RAD) method, which is a team-based information system development technique to accelerate the system development process so that the completion process is very short. The RAD method consists of four stages: the first stage of system requirements planning, the second stage of system user design, the third stage of system construction, and the last stage of cutover (Shelly & Rosenblatt, 2012). The implementation of the application of the RAD method in the development of a syariah cooperative savings and loan system application results in an analysis of system application requirements specifications, system application design analysis, system application construction design, and system application test implementation design using certain methods.